2021
DOI: 10.3892/etm.2021.10196
|View full text |Cite
|
Sign up to set email alerts
|

Potential protective effect of hesperidin on hypoxia/reoxygenation‑induced hepatocyte injury

Abstract: Hesperidin (HDN) has been reported to have hydrogen radical-and hydrogen peroxide-removal activities and to serve an antioxidant role in biological systems. However, whether HDN protects hepatocytes (HCs) against hypoxia/reoxygenation (H/R)-induced injury remains unknown. The present study aimed to explore the role of HDN in H/R-induced injury. HCs were isolated and cultured under H/R conditions with or without HDN treatment. HC damage was markedly induced under H/R, as indicated by cell viability, supernatant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…For the higher dose of HE, the clear overexpression of p62 throughout culture, together with no clear increase in LC3-IIB conversion despite increase in LC3 towards end of differentiation, ERK 1/2 phosphorylation reduction (at day 5) and a decrease in number of apoptotic cells suggest that HE may present the ability to prolong the survival of those cells; however, they are not able to sustain autophagy which can impair full osteoclast differentiation and function [40]. Li et al (2021) [41], evaluating the potential in vitro protective effect of HE (50 µg/mL) on hypoxia/reoxygenation (H/R)induced hepatocyte injury, found that the protein levels of autophagy markers LC3-IIB and Beclin-1 increased, while p62 levels decreased during H/R under exposure to HE. The authors suggested that HE induces autophagy to protect the hepatocyte against H/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…For the higher dose of HE, the clear overexpression of p62 throughout culture, together with no clear increase in LC3-IIB conversion despite increase in LC3 towards end of differentiation, ERK 1/2 phosphorylation reduction (at day 5) and a decrease in number of apoptotic cells suggest that HE may present the ability to prolong the survival of those cells; however, they are not able to sustain autophagy which can impair full osteoclast differentiation and function [40]. Li et al (2021) [41], evaluating the potential in vitro protective effect of HE (50 µg/mL) on hypoxia/reoxygenation (H/R)induced hepatocyte injury, found that the protein levels of autophagy markers LC3-IIB and Beclin-1 increased, while p62 levels decreased during H/R under exposure to HE. The authors suggested that HE induces autophagy to protect the hepatocyte against H/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Hesperidin (3, 5, 7-trihydroxyflavone 7-rhamnoglucoside) is the main polyphenol compound found in citrus fruits. This bioflavonoid exhibits antioxidant, anti-inflammatory, and antibacterial effects [ 14 , 15 ]. A recent study has demonstrated that hesperidin protected cells against redox imbalances [ 16 ].…”
Section: Introductionmentioning
confidence: 99%